Spotlight on ceritinib in the treatment of ALK+ NSCLC: design, development and place in therapy - Santarpia M; Daffinà MG; D'Aveni A; Marabello G; Liguori A; Giovannetti E; Karachaliou N; Gonzalez Cao M; Rosell R; Altavilla G (Dove Medical Press, 2017)
Mariacarmela Santarpia,1 Maria Grazia Daffinà,1 Alessandro D’Aveni,1 Grazia Marabello,1 Alessia Liguori,1 Elisa Giovannetti,2–4 Niki Karachaliou,5 Maria Gonzalez Cao,6 Rafael Rosell,7,8 Giuseppe Altavilla1 1Medical Oncology Unit, Department of Human Pathology “G. Barresi”, University of Messina, Messina, Italy; 2Department of Medical Oncology, VU University Medical Center, Amsterdam, The Netherlands; 3Department of Nanoscience and Nanotechnologies, CNR-Nano, Institute of Nanoscience and Nanotechnology, 4Cancer Pharmacology Lab, AIRC Start-Up Unit, University of Pisa, Pisa, Italy; 5Institute of Oncology Rosell (IOR), University Hospital Sagrat Cor, 6Oncology Department, Institute of Oncology Rosell (IOR), Quirón-Dexeus University Institute, Barcelona, 7Cancer Biology and Precision Medicine Program, Germans Trias i Pujol Research Institute, 8Catalan Institute of Oncology, Germans Trias i Pujol University Hospital, Badalona, Spain Abstract: The identification of echinoderm microtubule-associated protein-like 4 (EML4) and anaplastic lymphoma kinase (ALK) fusion gene in non-small cell lung cancer (NSCLC) has radically changed the treatment of a subset of patients harboring this oncogenic driver. Crizotinib was the first ALK tyrosine kinase inhibitor to receive fast approval and is currently indicated as the first-line therapy for advanced, ALK-positive NSCLC patients. However, despite crizotinib’s efficacy, patients almost invariably progress, with the central nervous system being one of the most common sites of relapse. Different mechanisms of acquired resistance have been identified, including secondary ALK mutations, ALK copy number alterations and activation of bypass tracks. Different highly potent and brain-penetrant next-generation ALK inhibitors have been developed and tested in NSCLC patients with ALK rearrangements. Ceritinib, a structurally distinct and selective ALK inhibitor, showed 20 times higher potency than crizotinib in inhibiting ALK and had activity against the most common crizotinib-resistant mutations, including L1196M and G1269A, in preclinical models. In Phase I and II studies, ceritinib demonstrated pronounced activity in both crizotinib-naïve and crizotinib-refractory patients, with responses observed regardless of the presence of ALK resistance mutations. Ceritinib was the first ALK inhibitor to be approved for the treatment of crizotinib-refractory, ALK-rearranged NSCLC, and recent results from a Phase III study have demonstrated superior efficacy compared to standard chemotherapy in the first- and second-line setting. We provide an extensive overview of ceritinib from the design of the compound through preclinical data until efficacy and toxicity results from Phase I–III clinical studies. We review the molecular alterations associated with resistance to ceritinib and highlight the importance of obtaining tumor biopsy at progression to tailor therapy based upon the underlying resistance mechanism. We finally provide an outlook on novel rational therapeutic combinations. Keywords: acquired resistance, anaplastic lymphoma kinase gene, non-small cell lung cancer, ALK tyrosine kinase inhibitors